2010
DOI: 10.4084/mjhid.2010.001
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis A to E in South Mediterranean Countries

Abstract: Viral hepatitis represents an important health problem in the South Mediterranean countries, Egypt, Libya, Tunisia, Algeria and Morocco. Emerging natural history and epidemiological information reveal differences in the overall epidemiology, risk factors and modes of transmission of viral hepatitis A, B, C, D, E infections in the South Mediterranean region. The differences in the in incidence and prevalence of viral hepatitis across North African countries is attributed to variations in health care and sanitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 83 publications
(109 reference statements)
6
26
1
Order By: Relevance
“…Prevalence of both HAV and HEV was higher in males than in females, this finding is consistent with other studies (Joon et al, 2015;Al-Naaimi et al, 2012;Kamal et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…Prevalence of both HAV and HEV was higher in males than in females, this finding is consistent with other studies (Joon et al, 2015;Al-Naaimi et al, 2012;Kamal et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…The epidemiologic pattern of HAV in a given country is therefore deduced primarily from seroprevalence data (Letaief et al 2005). In Tunisia, a number of studies found HAV prevalence rates ranging between 84.0 and 92 %; recently, a survey conducted to assess the prevalence of HAV among Tunisian children and adolescents revealed an overall seroprevalence of 60 % in this population (44 %, in children\10 years old, 58 % in those 10-15 years of age, and 83 % in adolescents with [15 years of age) (Kamal et al 2010). These data suggest that HAV endemicity in Tunisia has changed from high to intermediate/high.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are needed to determine the prevalence of HBV among the general population. The small number of subjects included in the studies we referred to might explain this variation; thus, larger more detailed studies are needed to gather reliable data [33][34][35][36].…”
Section: Hbv Among Pregnant Women In North African (Maghreb) Regionmentioning
confidence: 99%